2012
DOI: 10.1186/1756-8935-5-19
|View full text |Cite
|
Sign up to set email alerts
|

Mediator regulates non-coding RNA transcription at fission yeast centromeres

Abstract: BackgroundIn fission yeast, centromeric heterochromatin is necessary for the fidelity of chromosome segregation. Propagation of heterochromatin in dividing cells requires RNA interference (RNAi) and transcription of centromeric repeats by RNA polymerase II during the S phase of the cell cycle.ResultsWe found that the Med8-Med18-Med20 submodule of the Mediator complex is required for the transcriptional regulation of native centromeric dh and dg repeats and for the silencing of reporter genes inserted in centro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
0
14
1
Order By: Relevance
“…Recently, two reports showed that MHD was important for heterochromatin formation at pericentromeres [34], [35]. However, there are several discrepancies between their data and ours.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Recently, two reports showed that MHD was important for heterochromatin formation at pericentromeres [34], [35]. However, there are several discrepancies between their data and ours.…”
Section: Discussioncontrasting
confidence: 72%
“…Indeed, recent reports suggest a negative role of MHD subunits (Med18 and Med20) in heterochromatic transcription, based on the observation of an increase in the transcription of pericentromeric ncRNA in Mediator mutants [34], [35]. However, it is difficult to state conclusively whether the observed increase is due to the direct effects of the absence of Mediator because it is also possible that the deletion of Mediator subunits causes disruption of the heterochromatin, which secondarily induces an increase in transcription.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these mutants were deletions of two proteins that, although not annotated in PomBase as affecting chromatin silencing at centromeres, have previously been reported to have a modest impact on centromeric heterochromatin integrity: the mediator subunit Med20 [40], and CRL adaptor protein Ddb1 [27]. Aside from these two mutants whose centromeric silencing defects have already been characterised, we identified five mutants with no previously described effects on heterochromatin silencing.…”
Section: A Systematic Screen For Factors Required For Centromeric Hetmentioning
confidence: 93%
“…In the yeast S. pombe , Mediator has been linked to pericentromeric heterochromatin formation 143 . These studies suggest that Mediator functions by coordinating pol II-dependent ncRNA transcription with the RNAi machinery to help form and maintain heterochromatin domains 143-145 . Similarly, Mediator has been implicated in telomeric heterochromatin maintenance in the budding yeast S. cerevisiae .…”
Section: Mediator and Chromatin Architecturementioning
confidence: 98%